Hospital Urinary Tract Infections in Healthcare Units on the Example of Mazovian Specialist Hospital Ltd - Trześniewska-Ofiara, Zuzanna; Mendrycka, Mariola; Cudo, Andrzej; Szmulik, Magdalena; Woźniak-Kosek, Agnieszka (Frontiers in Cellular and Infection Microbiology, 2022)
Microbiological diagnostics is of great importance in limiting the spread of nosocomial infections. The information on etiological agents of infections and their susceptibility to antibiotics enables a quick response in the case of a suspected epidemic outbreak. The aim of this study is to analyze the incidence of nosocomial urinary tract infections among patients hospitalized in hospital wards over a period of 2 years and to determine the predominant etiological agent depending on the method of clinical specimen collection. Data from the Mazovian Specialist Hospital (MSH) in Radom constitute the material for the preparation of this study. Urine was collected using two methods. The first one was the method of collecting urine from the central stream, while the second method was urine collected from patients with a urinary catheter in place. The statistical calculations were conducted using the statistical software. Based on hospital data, it was shown that 5,870 urine tests were performed during the period under review, of which 2,070 were positive. The number of positive results in 2021 decreased by 2.84% compared to that in 2020. On the basis of the statistical analysis, differences in the occurrence of multiple strains were observed between catheter-based and midstream urine collection. Differences were observed especially for Acinetobacter baumannii, Candida albicans, Escherichia coli, and Pseudomonas aeruginosa. A. baumannii, C. albicans, and P. aeruginosa were significantly more frequently found in urine samples collected through the catheter than from the midstream. Furthermore, E. coli (51.56%) and Enterococcus species (25.46%) were more frequent when collected from the middle stream than when urine was collected through a catheter. However, for the strain K. pneumoniae, the results were comparable when urine was collected from catheterized patients (13.83%) and from midstream (13.35%). Urinary tract infection among hospitalized patients of the Mazovian Specialist Hospital in Radom was diagnosed quite frequently. In 2021, 32 more urine cultures were performed than in 2020. In the analyzed period, among all ordered urine cultures, 35.27% of samples were positive.